Pengadopsian Konsep Tax Amnesty dalam Program Pemutihan Pajak Kendaran Bermotor di Provinsi Jawa Barat Tahun 2025 - Diding Jalaludin; Nandang Najmudin (Jurnal Sosial Politik dan Hukum, 2025)
This research aims to analyse the principle of justice in the tax amnesty program implemented by the West Java Provincial Government in 2025 which eliminates principal arrears and fines of motor vehicle tax until the tax year 2024. The research method used is descriptive analysis method with normative juridical research approach. The data used is secondary data consisting of primary legal materials as an analysis knife in the form of laws and regulations related to tax amnesty regulations in Indonesia. The results of this research is that the taxation programme implemented in West Java Province should not only be seen from the aspect of PAD fulfilment, but the programme must consider the principles and theories of justice and adopt the concept of tax amnesty stipulated in Law Number 11 of 2016 concerning Tax Amnesty which is then categorised as regional tax amnesty and strengthened with an adequate legal basis for the creation of equitable tax collection.